Differences in dry sliding wear behavior between HVAF-sprayed amorphous steel and crystalline stainless steel coatings. Issue 5 (May 2019) - Guo, Hui; Zhang, Suode; Sun, Wenhai; Wang, Jianqiang
Abstract: Dry sliding wear behavior of amorphous steel coating (ASC) and crystalline stainless steel coating (SSC) manufactured by high-velocity-air-fuel-spraying was investigated. With increasing normal load, coefficient of friction (COF) of ASC decreases slightly from 0.78 to 0.69. COF of SSC presents a minor difference under various normal loads but increases with sliding time accompanied by relatively large fluctuation. Such a difference in friction behavior between such two coatings can be understood based upon the roles of shear stress and flash temperature. Wear rate of SSC is much higher than that of ASC, suggesting better wear resistance of ASC. The enhanced wear resistance is correlated with high hardness ( H ), reduced Young's modulus ( E r ), and ratios of H / E r and H 3 / E r 2 . Detailed analyses on worn surfaces and sub-surfaces indicate that the wear mechanisms for ASC include delamination, abrasive and oxidation wear, whereas those for SSC are delamination and oxidation.